Pertanggungjawaban Pidana Bagi Anggota Militer Yang Melakukan Tindak Pidana Penganiayaan Secara Bersama-Sama Yang Mengakibatkan Luka Berat di Wilayah Hukum Pengadilan Militer III-15 Kupang : Studi Putusan Nomor 17-K/PM.III_15/Al/2023 - Andini Zaskia Karim; Daud Dima Tallo; Heryanto Amalo (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
This study aims to find out and analyze criminal liability for military members who commit criminal acts of persecution together that result in serious injuries in the Jurisdiction of the Military Court III-15 Kupang. This research uses an empirical juridical approach, which is research whose data is obtained through efforts to investigate the reality in social life. The results of the study show that criminal liability in the Crime of Persecution committed by Military Members against civilians is resolved according to military disciplinary sanctions, namely temporary detention and administrative sanctions, and is also resolved by criminal sanctions, namely the Defendants are subject to 351 paragraph (2) Jo Article 55 paragraph (1) to 1 of the Criminal Code with a prison sentence of Defendant-1 for 1 (one) year and 2 (two) months, Defendant-2 for 10 (ten) months and Defendant-3 for 8 (eight) months is reduced as long as the Defendants are in temporary custody. The Judge's consideration in imposing a verdict on the criminal act of persecution against civilians based on decision number 17-K/PM. III_15/AL/2023 uses 2 (two) types of considerations, namely Juridical Balance, which is based on the indictment of the Military Inspector, the testimony of witnesses, the testimony of the defendants, and also the existence of several pieces of evidence, while the consideration of Non-Juridical considerations is based on matters that can be aggravated and things that can be mitigated.